KEWIRAUSAHAAN RAMAH LINGKUNGAN : UPAYA MENCIPTAKAN KESEIMBANGAN BISNIS BERKELANJUTAN PADA KEWIRAUSAHAAN MAHASISWA - Simajuntak, Dewi Fransiska; Wijaya, Redo Tridinata; Erik, Erik; Widyastuti, Liza Yudhita; Anugerah, Muhammad Davin; Putri, Cahya Nisrina Kamila (Universitas Negeri Jakarta, 2025)
Psychoeducation on the Implementation of Environmentally Friendly Green Entrepreneurship for MSMEs (Micro, Small, and Medium Enterprises) run by UNJ Students and Alumni in the food production sector, namely Dath Crumbs and Juragan Dimsum, as well as in the artificial flower arrangement service business, By.Paeonia. This activity was also attended by several students who are interested in entrepreneurship. This community service program was carried out to raise awareness among UNJ students and alumni entrepreneurs of the role they can play in protecting the environment while striving to gain profit from their businesses. We aim to foster awareness of environmental issues starting from our closest surroundings. The education we provided began with the introduction of the concept of green entrepreneurship, the importance of sustainability awareness among business actors, and the application of ecopreneurship in the food, beverage, and artificial flower industries. In this seminar, we also discussed the benefits that entrepreneurs can obtain by applying ecopreneurship. Moreover, as part of the younger generation, their businesses are more likely to endure in the long term. The mean score showed an improvement of 0.40 from the pretest to the posttest. Therefore, we hope that these entrepreneurs will eventually become green entrepreneurs and ecoinnovators—a generation that contributes ideas for running sustainable businesses in order to achieve SDG 12: Responsible Consumption and Production.